IgG-like Bispecific Antibody CD3×EpCAM Generated by Split Intein Against Colorectal Cancer - Wang, Lei; Qiao, Yu; Zong, Huifang; Han, Lei; Ke, Yong; Pan, ZhiDi; Chen, Jie; Lu, Jun; Li, Jinyao; Ying, Tianlei; Zhang, Baohong; Zhu, Jianwei (Frontiers in Pharmacology, 2022)
Background: Colorectal cancer is a commonly diagnosed cancer with high mortality worldwide. Postoperative recidivation and metastasis still are the main challenges in clinical treatments. Thus, it is urgent to develop new therapies against colorectal cancer. Epithelial Cell Adhesion Molecule (EpCAM) is overexpressed in colorectal cancer cells and strongly associated with cancer development. Bispecific antibody (BsAb) is a kind of promising immunotherapy, which could recognize T cells and cancer cells simultaneously to achieve the anti-tumor effects. Methods: A bispecific antibody targeting EpCAM and CD3 with IgG format was genereated by split intein based on the Bispecific Antibody by Protein Splicing" platform. In vitro, the affinity of CD3×EpCAM BsAb was determined by Biolayer interferometry, its cytotoxicity was detected by LDH release assay, T cell recruitment and activation was detected by Flow Cytometry. In vivo, its pharmacokinetic parameters were detected, and anti-tumor effects were evaluated on the tumor cell xenograft mouse model. Results: The results showed that the CD3EpCAM BsAb could activate and recruit T cells via binding colorectal cells and T cells, which could lead to more potent cytotoxicity to various colorectal cell lines than its parent EpCAM monoclonal antibody (mAb) in vitro. The CD3EpCAM BsAb had similar pharmacokinetic parameters with EpCAM mAb and inhibits tumor growth on the SW480 tumor cell xenograft mouse model. Conclusion: The CD3×EpCAM BsAb could be a promising candidate for colorectal cancer treatment.